IMMUNOHISTOCHEMICAL STUDY OF MICROVESSELS OF HUMAN SPHENOIDAL SINUS MUCOSA USING CD34 MARKER - Совгиря, С.М.; Винник, Н.І.; Тихонова, О.О.; Тарасенко, Я.А. (World of Medicine and Biology, 2015)
The results of immunohistochemical studies of different parts of human sphenoid sinus mucosa using the marker CD34 suggests that in the sphenoid sinus mucosa there is a different type of microcirculation. Thus, in the mucosa of the medial and lateral walls of the microvessels are of arcade structure, in the mucosa of the front and bottom walls it is steeple and in the growth areas of rear wall the phenomena of angiogenesis are often found.